Measurement of Tibial Bone Length and Body Weight as Factors that Determine The Running Speed of 5th Grade Elementary School Students - Siti Munawaroh; Aisyah Nooratisya; Didik Gunawan Tamtomo (Smart Society Empowerment Journal, 2022)
Introduction: Improving the quality of human resources in the field of sports needs to be done by coaching from an early age. One of the things that can be done is to find and identify the talents possessed by elementary school students to find out the potential for sports that are following the child's talents. Running is an important sport in early school development. In the 100 meter sprint, runners try to achieve maximum speed, one of which is influenced by body structure. The longer the legs, the faster they run. On the other hand, with a child's weight, the greater the weight, the slower it tends to be. This research aims to determine the effect of tibia bone length and body weight on running speed.Methods: The activity was carried out at the State Elementary School 15 Mangkubumen Lor Surakarta. Class V. There were 33 students involved in the measurement of the foot length and weight. The data obtained were analyzed using multiple linear regression. The results of the analysis are used as educational material and input for sports teachers at the school.Results and discussions: The average leg length was 30.51 cm and the average weight was 36.33 Kg. While the average running speed is 4.74 m/s. Statistical test of the regression coefficient showed that leg length (β = 0.424; p = 0.018) and body weight (β = -0.488; p = 0.007) means that these two components have an effect on running speed.Conclusion: Leg length has a positive effect while weight has a negative effect on running speed.